Implementing a simple pharmacovigilance program to improve reporting of adverse events associated with biologic therapy in rheumatology: Preliminary results from the Calabria Biologics Pharmacovigilance Program (CBPP) - Palleria, Caterina (PLoS One, 2018)
INTRODUCTION: Post-marketing surveillance activities (namely pharmacovigilance) are crucial to favor the early detection of unexpected adverse events (AEs) and/or serious adverse reactions (SAEs). Indeed, spontaneous reporting of AEs has been demonstrated to underestimate the number of events in different clinical settings. Aim of the present study is to report the preliminary data of a Regional (Calabria, Italy) Pharmacovigilance Program (CBPP) aimed at improving AEs’ reporting associated with biologics use in rheumatology. MATERIALS AND METHODS: We developed a simple, cost-effective pharmacovigilance program based on regular training sessions for physicians (stimulated reporting), periodical phone calls by a clinical pharmacologist aimed at identifying new events and stimulating self-awareness and encouraging reporting to the physician during the subsequent follow-up visit for minor AEs. To test this approach, all consecutive patients undergoing treatment with one biologic agent at eight rheumatology centers during a two-years period were invited to participate. Collected AEs were compared to the number of AEs spontaneously reported for the same molecules in the same centers before starting the protocol. RESULTS: During the study period, 399 patients (245 females; mean age: 58 ± 11 years) were started on treatment with biologics for active RA (n = 211, 52.9%), PsA (n = 119, 29.8%) or AS (n = 69, 17.3%) at eight rheumatology centers. A total of 125 AEs (31.3%) and 9 SAEs (2.3%) were reported during the two-years study period. In the control cohort (comprising 368 consecutive patients started on treatment with bDMARDs during a two-years period before CBPP study) only 42 (11.4%) AEs and no SAEs were reported (p < 0.0001). The most common AEs were injection site reactions and skin disorders. CONCLUSIONS: In conclusion, our study provides further evidence of a critical role of active pharmacovigilance in detection, reporting and analysis of AEs in rheumatology.